Impact of clinicopathologic features on leptomeningeal metastasis from lung adenocarcinoma and treatment efficacy with epidermal growth factor receptor tyrosine kinase inhibitor. Issue 2 (7th January 2020) - Kwon, Byoung Soo; Cho, Young Hyun; Yoon, Shin‐Kyo; Lee, Dae Ho; Kim, Sang‐We; Kwon, Do Hoon; Lee, Jae Cheol; Choi, Chang‐Min
Abstract: Background: We investigated the risk factors for leptomeningeal carcinomatosis (LMC) and compared clinical efficacies of various treatment modalities including intrathecal (IT) chemotherapy in patients with lung adenocarcinoma harboring epidermal growth factor receptor (EGFR) mutations. Methods: Using clinical research data from the Asan Medical Center, we retrospectively analyzed data of patients diagnosed with LMC, confirmed via cerebrospinal fluid (CSF) analysis from January 2008 to December 2017. Results: We identified 1189 patients with lung adenocarcinoma harboring EGFR mutations. Among these, 9.8% had a median duration of 13.5 (interquartile range [IQR] 6.8–23.6) months from the initial lung cancer diagnosis to LMC occurrence. Younger age (hazard ratio [HR] 1.043, P < 0.001), initial metastatic disease (HR 3.768, P < 0.001), and metastasis to the brain (HR 8.682, P < 0.001) or lung (HR 2.317, P = 0.004) were risk factors associated with LMC. Median survival duration from LMC diagnosis was 3.8 (IQR 1.5–8.6) months. Eastern Cooperative Oncology Group performance status score ≤ 2 (HR 0.505, P = 0.007) and insertion of Ommaya reservoir (HR 0.445, P = 0.005) were associated with longer survival. EGFR‐tyrosine kinase inhibitor (TKI) conferred survival benefits compared to cytotoxic chemotherapy or best supportive care (HR 2.222, P = 0.018; HR 5.638, P < 0.001, respectively). Although IT chemotherapy showed no survival benefit, it was associated with improved neurologic symptoms and signs and CSF negative conversion. Conclusions: Younger age, initial diagnosis of metastatic disease, and metastasis to the brain or different lobes were associated with LMC in patients with EGFR‐mutant lung adenocarcinoma. Therapeutic interventions including EGFR‐TKIs, cytotoxic chemotherapy, or Ommaya reservoir, and good performance status were related to favorable survival outcomes. Key points: Age and disease status were associated with LMC in patients with EGFR‐mutant adenocarcinoma, and EGFR‐TKI, Ommaya reservoir, and good performance status were related to survival benefit.